Karakteristik gambaran sitologi pap-smear sebagai tes skrining untuk lesi pra-kanker serviks di RSUP Sanglah, Denpasar, Bali - Putu Risky Yoga Pradnyana; Anak Agung Ayu Ngurah Susraini; I Gusti Ayu Sri Mahendra Dewi (Intisari Sains Medis, 2019)
Background: Cervical cancer is the second most often cancer that occurs in women worldwide after breast cancer and as many as 84% of the cases occur in developing countries. Pap Smear is a screening method that widely used for cervical cancer screening. The aim of the study is to obtain the characteristic data of pap smear cytology as a pre-cervical cancer screening in Sanglah General Hospital 2016 – 2017 period.Methods: This study was descriptive research with cross sectional study design. The sampling technique is total sampling where the research data comes from the cytology registration book results of the Anatomical Pathology Laboratory at Sanglah General Hospital Denpasar 1 January 2016 - 31 December 2017 period which has fulfilled the inclusion criteria and does not meet the exclusion criteria. Data were analyzed using SPSS version 20 for Windows.Results: This study collected as many as 590 samples. Most of the pap smear patients at Sanglah General Hospital Denpasar were 41-50 year old group as many as 188 people (31.86%), most of the patients parities were nullipara parities as many as 324 people (54.92%), most had no complaints as many as 261 people (44.24%) and most of the pap smear cytology description was Reactive Cellular Changes Associated with Inflammation (RCCI) as many as 261 people (44.64%).Conclusion: Most of the respondents who underwent pap-smear test as a screening step for pre-cancerous lesions had a cytological picture of Reactive cellular changes associated with Inflammation (RCCI)